NEEDS ANALYSIS FOR DEVELOPING SCIENCE TEACHING MODULES TO IMPROVE ENVIRONMENTAL AWARENESS OF GRADE VIII STUDENTS IN SCHOOLS - Rachman, Muhamad Taufik; Aripin, Aripin; Ramdani, Dani; Hernawati, Diana; Badriah, Liah (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to comprehensively analyze the needs (Define stage) in developing a Natural Science (IPA) teaching module aimed at increasing environmental awareness of Grade VIII junior high school students. This study adopted the Research and Development (R&D) method, focusing on the Needs Analysis stage of the 4-D model (Define). Data collection was conducted through teacher interviews and distribution of needs analysis questionnaires to students and teachers. The research subjects consisted of Grade VIII students and three science teachers in a public junior high school. The results confirmed a significant gap between ideal learning conditions and current practices. The main findings indicated a very high need (90.20%) for a module that integrates in-depth learning, as current teaching methods are largely conventional, evidenced by the lowest score in the method aspect (38.24%). Furthermore, despite high initial awareness (84.31% and 63.97%), the learning materials lacked a specific module on Climate Change and failed to fully transform knowledge into active ecological behavior. This study strongly concludes that contextual, interactive, and technology-integrated science teaching modules are urgently needed to facilitate reflective thinking, encourage active ecological behavior, and bridge the gap between conceptual mastery and practical environmental responsibility in Grade VIII students.